Self-concept and academic performance: A review of Hispanic literature (Revista INTEREDU11, 2021)
This article corresponds to a review of twenty studies focused on researching the various relationships between students’ self-concept and their academic performance. The search focused on studies published in Castilian language present in various databases. The organization of the information considered the categorization of all participants as a criterion. The results suggest that studies generally show relationships between self-concept and academic performance, where self-concept would be only one out of many factors which affect academic performance, and such relationships would be affected by certain conditions, such as gender, educational context, and disability status, just to mention few of them. These findings are highly relevant for the design of strategies to do improve academic performance which consider the students’ self-concept.